2005
DOI: 10.1101/lm.51305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of post-training hippocampal injections of midazolam on fear conditioning

Abstract: Benzodiazepines have been useful tools for investigating mechanisms underlying learning and memory. The present set of experiments investigates the role of hippocampal GABA A /benzodiazepine receptors in memory consolidation using Pavlovian fear conditioning. Rats were prepared with cannulae aimed at the dorsal hippocampus and trained with a series of white noise-shock pairings. In the first experiment, animals received intrahippocampal infusion of midazolam or vehicle immediately or 3 h after training. Then, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Moreover, prior administration of an antagonist of BDZ sites reversed BDZ-induced amnesia (Savic et al, 2005) whereas the administration of the inverse agonist resulted in a promnesic effect, indicating that BDZ sites are implicated in the formation of memory. BDZ's disruptive effect has been observed following administration either pre-or posttraining in diverse learning and memory paradigms (Gafford et al, 2005). Such an effect was also reported after both BDZ intraamygdala (Dickinson-Anson and McGaugh, 1993) and BDZ intradorsal hippocampus (Gafford et al, 2005) infusions.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Moreover, prior administration of an antagonist of BDZ sites reversed BDZ-induced amnesia (Savic et al, 2005) whereas the administration of the inverse agonist resulted in a promnesic effect, indicating that BDZ sites are implicated in the formation of memory. BDZ's disruptive effect has been observed following administration either pre-or posttraining in diverse learning and memory paradigms (Gafford et al, 2005). Such an effect was also reported after both BDZ intraamygdala (Dickinson-Anson and McGaugh, 1993) and BDZ intradorsal hippocampus (Gafford et al, 2005) infusions.…”
Section: Introductionmentioning
confidence: 77%
“…BDZ's disruptive effect has been observed following administration either pre-or posttraining in diverse learning and memory paradigms (Gafford et al, 2005). Such an effect was also reported after both BDZ intraamygdala (Dickinson-Anson and McGaugh, 1993) and BDZ intradorsal hippocampus (Gafford et al, 2005) infusions. Consistent with such findings, Bustos et al (2006) have recently demonstrated that midazolam (MDZ), a short-acting BDZ, affects fear memory reconsolidation.…”
Section: Introductionmentioning
confidence: 77%
“…The lack of generalization in Gad65 ‫מ/+‬ mice appears to argue against this, but it should be considered that adult heterozygotes display normal GABA content in the amygdala and hippocampus (Stork et al 2000). Second, GAD65 regulation and function may differ between subpopulations of GABA interneurons, which are characterized by particular morphology, physiology, and expression of neurochemical factors (Freund and Buzsáki 1996;Frenois et al 2005;Mascagni and McDonald 2007;Muller et al 2007) and are thought to mediate specific aspects of fear memoryrelated information processing within the amygdala (e.g., Quirk et al 2003;Azad et al 2004;Marowsky et al 2005) and hippocampus (Crestani et al 1999;Gafford et al 2005). Third, if compensatory mechanisms are active in the Gad65 null mutants, then the inability of these animals to change GABAergic function via regulation of GAD65 expression may be important.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these findings, it is also interesting that spike-timingdependent LTP in the amygdala is tightly controlled by the level of GABAergic inhibition (Shin et al 2006). Concerning the hippocampus, it has been shown that deficits in GABA A receptor clustering increase anxiety in mutant mice heterozygous for the ␥2 subunit of the GABA A receptor (Crestani et al 1999) and that post-training injection of the benzodiazepine midazolam interferes with context memory consolidation (Gafford et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Fanselow and Helmstetter (1988) found that pre-training midazolam administration attenuated conditioning as shown by subsequent freezing to the context associated with shock. The hippocampus seems to be one site of action for this effect, since immediate post-conditioning application of midazolam to the dorsal hippocampus reduced subsequent contextor cue-induced freezing (Gafford et al 2005). Passive avoidance studies are in substantial agreement in showing that pre-conditioning administration of an anxiolytic benzodiazepine impairs acquisition of the avoidance response in rats and mice (Anglade et al 1994;Broekkamp et al 1984;Cryan et al 2004;Jensen et al 1979;Nagatani and Yamamoto 1991;Oishi et al 1972;Patel et al 1979).…”
Section: Discussionmentioning
confidence: 94%